Case Report: Fatal Acute Liver Failure With Giant Cell Transformation in a Pediatric Patient Associated With MIS-C - Bonilla Gonzalez, Carolina; Hincapié Echeverría, Marcela; Plazas Pachón, Rocio; Mora Umaña, Paola; Diaz Gómez, Berlly Lucia; Gualdron Barreto, Nathalie (Frontiers in Pediatrics, 2022)
We describe the first pediatric case of a 10-month-old boy with MIS-C who developed fulminant acute liver failure with associated giant cell transformation and a fatal outcome, after ruling out other infectious, metabolic, genetic, and autoimmune causes of liver failure following the usual algorithms for approaching the etiology. Although the patient received the main treatment strategies for liver failure, the patient had a fatal outcome. A clinical autopsy was considered as part of the diagnostic approach, which showed evidence of giant cell transformation.